(untitled) (Encuentros, 2016)
The revolutions are a central phenomenon in the characterization of modern history. Its consequences are evident since the late eighteenth century to the Thirteen Colonies and France, to the examples provided by the XX. Such an assessment has been subjected to studies of various kinds; however, they not all neatly explained the relationship is implied in its courses with the science of law. This review article aims to systematize and theoretically integrate inherent in the revolution content as transcendent form of political resistance, by assessing their supporting elements and constitutive dimension of its scope for political and legal sciences, and his involvement with the factor of historical evolution. Keywords: modernity, progress, violence, revolution.